WORK-FROM-HOME SETUP AND AUDIT QUALITY AMONG EXTERNAL AUDITORS - Aguilar, Lord Eddie Indac; Alcantara, Jessa Mae Rome; Camoro, Airah Yvonne Tormis; Olanolan, Alexiz John Inocentes (Jurnal Akuntansi Kontemporer, 2024)
Research Purposes. Technological advancement and globalization increase demand for flexible work arrangements, particularly remote working, which pose limitations and challenges to auditors in maintaining audit quality. The study aims to determine which domain of work-from-home setup significantly influences the audit quality of external auditors. Research Methods The study used quantitative research design and correlational techniques to test the relationship and significance of the variables. It was participated by CPAs in public practice who experienced remote auditing and employed the random sampling technique in selecting the respondents. The data were analyzed and interpreted using the mean, standard deviation, Pearson's correlation, and regressionResearch Results and Findings. The results concluded that the effectiveness of work-from-home setup and audit quality have a moderately strong, positive correlation. Only the propensity to work remotely and work-life balance significantly influenced the audit quality of external auditors. The findings imply that despite the physical absence and changes in processes, working from home can be an effective work setup in attaining and maintaining high-quality audits and has the potential to address the demand for flexible work arrangements if appropriately administered. The study suggests strengthening remote audits by creating and utilizing online tools for managing audit activities, such as submission of evidence, planning, and audit preparation.